MODERN MECHANISMS AND APPROACHES OF MANAGEMENT OF FOREIGN INVESTMENT FLOWS (Marketing Journal, 2025)
This article explores the modern theoretical foundations and practical models for attracting foreign direct investment (FDI) into a national economy. The study substantiates the application of the OLI model, competitive advantage theory, and the "flying geese" paradigm in managing investment flows. Uzbekistanʼs experience is analyzed in comparison with international frameworks, and effective strategic directions are proposed.
Keywords: foreign direct investment; FDI; economic growth; OLI model; competitive advantage; investment environment; strategy; Uzbekistan